Impact of ketogenic and fast-mimicking diet in gastrointestinal cancer treatment - Colombo, Elisa; Righini, Margherita; Balendra, Vyshnavy; Rustamli, Konul; Garrone, Ornella; Ratti, Margherita; Ghidini, Michele (Frontiers in Oncology, 2025)
Growing evidence suggests that both the ketogenic diet (KD) and the fast-mimicking diet (FMD) may have significant therapeutic effects in the treatment of gastrointestinal (GI) cancers. KD, characterized by a high fat intake and low carbohydrate intake, induces a state of ketosis that alters energy metabolism, reducing the availability of energy for cancer cells and slowing their growth. Similarly, FMT, which simulates the effects of fasting without requiring complete food abstention, has been studied for its potential to enhance immune response, reduce inflammation, and stimulate autophagy, contributing to the removal of damaged cells. Preclinical and clinical studies indicate that both dietary strategies may enhance the efficacy of chemotherapy while reducing the side effects associated with conventional treatments. Despite these promising findings, few studies have investigated the potential impact of these diets on anticancer treatment of gastrointestinal cancers, and further studies are necessary to better understand the biological mechanisms and to evaluate the safety and effectiveness of these strategies in broader clinical settings. With our review, we aim to analyze the available literature on KD and FMD and their role in the treatment of GI cancers.